Rediscovery of penicillin of psychiatry: haloperidol decanoate - Nazan Aydın; Hasan Mervan Aytaç; Esra Yazıcı; Doğan Yılmaz; Pınar Çetinay Aydın; Gökşen Yüksel Yalçın; Yücel Kadıoğlu; Cana Canbay; Merve Terzioğlu; Onur Şenol; Cavide Çakmak; Aysel Özer (Psychiatry and Clinical Psychopharmacology, 2019)
BACKGROUND: Haloperidol has been used as an effective antipsychotic for many years and continues to be one of the first options in difficult patients who require parenteral therapy in the acute phase. However, the depot form is less preferred in the treatment of patients with non-adherence among these patients whose clinical stabilization has been achieved by using parenteral haloperidol in the acute phase. Therefore, updating the information about the side effects of the depot form of haloperidol, which is still an effective treatment option, will be useful in reconsidering the position of this medicine among new and different options. METHODS: A total of 54 schizophrenic patients with severe symptoms and poor adherence to treatment who were hospitalized and treated with depot haloperidol following an acute stabilization period were included in this study. First, the Structured Clinical Interview for DSM-IV Axis I disorders (SCID-CV) was used to confirm the diagnosis, the Brief Psychiatric Rating Scale (BPRS), Scale for the Assessment of Positive Symptoms (SAPS) and Scale for the Assessment of Negative Symptoms (SANS) to assess the clinical severity and Global Assessment of Functioning (GAF) to assess the functionality. The Simpson-Angus Scale (SAS) was used to assess extrapyramidal side effects. With the exception of Visit 0, plasma haloperidol levels were measured at all visits. Also, measurements of waist circumference and weight, plasma fasting blood glucose, triglyceride, HDL, iron, haemoglobin (Hgb), prolactin (PRL) and HbA1c were also used for evaluation of the metabolic effects. RESULTS: Significant improvements were observed in the BPRS, SANS, SAPS scores in the long-term follow-up with the depot haloperidol treatment. While the dosage decreased over time, the plasma levels remained changed, and symptom improvement was maintained. No signs such as neuroleptic malignant syndrome or acute dystonia were observed and SAS scores were within acceptable limits during the treatment (μ = 1.40 ± 2.55). There is no statistically significant difference between measurements of the weight even there was a significant difference between three of the waist circumference values (p = 0.987). The first measurement of the waist circumference is statistically significantly higher than both the mid-measurement and the final measurement, interestingly (p = 0.002). When fasting blood glucose, triglyceride, HDL, iron, Hgb, PRL and HbA1c were measured at different times throughout the study, only prolactin levels increased significantly over time with the use of haloperidol (p < 0.001). At the end of a year, 50% of the patients participating in the study still continued to use the haloperidol decanoate. This means also that half of the patients had stopped to use haloperidol decanoate. However, only 18.5% of them (n = 5) discontinued use of this drug because of extrapyramidal side effects. CONCLUSION: Depot haloperidol remains an effective treatment option that improves treatment compliance in challenging schizophrenia patients with severe symptoms. The long-term metabolic and extrapyramidal side effect profile of the patients were generally within the safe limits with the use of haloperidol depot. According to the obtained data, the depot haloperidol continues to be a reliable treatment option in terms of adverse effects in the maintenance treatment of schizophrenia patients with severe symptoms and poor adherence to treatment.